Turing und Kryptografie - Blömer, Johannes (Informatik-Spektrum)
Ich beschreibe die deutsche Enigma-Verschlüsselungsmaschine und skizziere, wie sie von den Codebrechern von Bletchely Park um Alan Turing gebrochen wurde. Besonderes Augenmerk lege ich auf die Beiträge Alan Turings und die Bedeutung seiner Leistung für die Entwicklung moderner Kryptografie.

On black-box models of computation in cryptology - Jager, Tibor

On the Security of TLS-DHE in the Standard Model - Jager, Tibor; Kohlar, Florian; Schäge, Sven; Schwenk, Jörg (Advances in Cryptology - CRYPTO 2012 - 32nd Annual Cryptology Conference, Santa Barbara, CA, USA, August 19-23, 2012. Proceedings)

Tightly Secure Signatures and Public-Key Encryption - Hofheinz, Dennis; Jager, Tibor (Advances in Cryptology - CRYPTO 2012 - 32nd Annual Cryptology Conference, Santa Barbara, CA, USA, August 19-23, 2012. Proceedings)

Bleichenbacher's Attack Strikes again: Breaking PKCS#1 v1.5 in XML Encryption - Jager, Tibor; Schinzel, Sebastian; Somorovsky, Juraj (Computer Security - ESORICS 2012 - 17th European Symposium on Research in Computer Security, Pisa, Italy, September 10-12, 2012. Proceedings)

Waters Signatures with Optimal Security Reduction - Hofheinz, Dennis; Jager, Tibor; Knapp, Edward (Public Key Cryptography - PKC 2012 - 15th International Conference on Practice and Theory in Public Key Cryptography, Darmstadt, Germany, May 21-23, 2012. Proceedings)

Proving Linearizability of Multiset with Local Proof Obligations - Travkin, Oleg; Wehrheim, Heike; Schellhorn, Gerhard (ECEASST)

Model evolution and refinement - Ruhroth, Thomas; Wehrheim, Heike (Sci. Comput. Program.)

How to Prove Algorithms Linearisable - Schellhorn, Gerhard; Wehrheim, Heike; Derrick, John (Computer Aided Verification - 24th International Conference, CAV 2012, Berkeley, CA, USA, July 7-13, 2012 Proceedings)

Long term higher urinary calcium excretion within the normal physiologic range predicts impaired bone status of the proximal radius in healthy children with higher potential renal acid load - Shi, Lijie; Libuda, Lars; Schönau, Eckhard; Frassetto, Lynda; Remer, Thomas (Bone)

Dietary fatty acid intake, its food sources and determinants in European adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. - Vyncke, KE; Libuda, Lars; De Vriendt, T; Moreno, LA; Van Winckel, M; Manios, Y; Gottrand, F; Molnar, D; Vanaelst, B; Sjöström, M; González-Gross, M; Censi, L; et al. (Br J Nutr)

Beverage consumption among European adolescents in the HELENA study. - Duffey, KJ; Huybrechts, I; Mouratidou, T; Libuda, Lars; Kersting, M; De Vriendt, T; Gottrand, F; Widhalm, K; Dallongeville, J; Hallström, L; González-Gross, M; De Henauw, S; et al. (Eur J Clin Nutr)

Computer science and society as a field of computer science - Engbring, Dieter; Selke, Harald
In this article we report on the experiences of a redesigned teaching in the field of computer science and society (IuG). The reasons for the redesign and the concept are outlined. We have condensed our experiences into theses: 1. Computer science and society should be a compulsory course in the bachelor's degree, in which students get an overview of which social framework conditions are relevant for them and how they can be incorporated into practice. 2. Historical contents of computer science are to be processed here by considering current developments in the context of their genesis.

User Centered Design of an Interactive Mobile Assistance and Supervision System for Rehabilitation Purposes - Klompmaker, Florian; Workowski, Anke; Thronicke, Wolfgang; Ostermair, Florian; Willemsen, Detlev; Hoffmann, D

Towards Multimodal 3D Tabletop Interaction using Sensor Equipped Mobile Devices - Klompmaker, Florian; Nebe, Karsten; Eschenlohr, Julien

The technical potential of digital boards - Selke, Harald; Winkelnkemper, Felix
This article explains the technical potential of digital boards with which more and more schools are being equipped. A consideration of current usage scenarios of these interactive whiteboards shows that a large part of this potential is still unused and the deficits of the software often have to be circumvented with tricks, especially for use in demanding, student-oriented lessons. Finally, the further development of existing teaching scenarios using this technical potential shows that considering the technical possibilities of digital boards can motivate new didactic scenarios.

Der Qualitätsstandard für Usability Engineering der German UPA - Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut

Base Requirements for Virtual Tabletop Groupware Artifacts - Tobias, Müller; Nebe, Karsten; Klompmaker, Florian

Collaborative work on interactive displays - design, operation and fields of application - Fischer, Holger Gerhard; Klompmaker, Florian (M & C, humans and computers)

Das Heinz Nixdorf Institut: Über 25 Jahre interdisziplinär erfolgreich - Keil, Reinhard